2014
DOI: 10.1007/s00466-014-1006-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct finite element computation of non-linear modal coupling coefficients for reduced-order shell models

Abstract: International audienceWe propose a direct method for computing modal coupling coefficients - due to geometrically nonlinear effects - for thin shells vibrating at large amplitude and discretized by a finite element (FE) procedure. These coupling coefficients arise when considering a discrete expansion of the unknown displacement onto the eigenmodes of the linear operator. The evolution problem is thus projected onto the eigenmodes basis and expressed as an assembly of oscillators with quadratic and cubic nonli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 44 publications
0
66
0
Order By: Relevance
“…There are many strategies, allowing a MEAN-NL-ROM to be established, depending on the choice of the vector basis (see for instance [20]) or the way to extract the reduced operators from explicit construction [21,22] or from an implicit non intrusive construction [12,20]. In the present context, the MEAN-NL-ROM is explicitly constructed from the knowledge of the projection basis.…”
Section: Numerical Aspects For the Construction Of The Nonlinear Redumentioning
confidence: 99%
“…There are many strategies, allowing a MEAN-NL-ROM to be established, depending on the choice of the vector basis (see for instance [20]) or the way to extract the reduced operators from explicit construction [21,22] or from an implicit non intrusive construction [12,20]. In the present context, the MEAN-NL-ROM is explicitly constructed from the knowledge of the projection basis.…”
Section: Numerical Aspects For the Construction Of The Nonlinear Redumentioning
confidence: 99%
“…This procedure has been investigated for the analysis of nonlinear vibration of piezoelectric layered beams with applications to NEMS [22]. A more general theory for finite-element models with geometric nonlinearity was provided by Touzé et al [23] with applications to reduced-order models by using 'Mixed Interpolation of Tensorial Components' (MITC) shell elements. Here we adopt this method for characterization of nonlinear resonators, which is applicable at macro and micro scales.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, a highly desirable future goal is to determine the nonlinear coupling coefficients numerically, e.g. by using finite element formulations of the strain energy 46 , and thus provide simulative predictions of mode coupling during device design. In essence, our work has shown that fundamental nonlinear phenomena such as SPDC occur in mechanical structures where two prerequisites are given: The vibrational modes of the structure must fulfil an internal resonance condition on one hand and have a reasonably large coupling on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…and includes three-and four-wave terms of the form α n,m,l q n q m q l and β n,m,l,k q n q m q l q k , respectively 46 . Out of all possible three-and four-wave mixings, we consider only the resonant terms between the drive mode and the two parasitic modes since these are the most relevant ones in our high-Q system.…”
Section: System Modelmentioning
confidence: 99%